2020
DOI: 10.1186/s43055-020-00185-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of central veins using susceptibility weighted imaging (SWI) for discrimination between lesions in multiple sclerosis (MS) and cerebral small vessel disease (CSVD)

Abstract: Background: Conventional brain MRI cannot always distinguish between different white matter lesions. Susceptibility weighted imaging (SWI) can detect a sign called central vein sign which is suggested to discriminate between multiple sclerosis and other white matter lesions thus increasing the accuracy of MRI in MS diagnosis. This study aimed to evaluate the role of MR susceptibility weighted imaging in differentiating MS from CSVD lesions. Results: The central vein sign (CVS) was found to have a premium diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…The mean percentage of CV-positive lesions was significantly higher in patients who received a CDMS diagnosis from the TC and ATC groups as compared to patients who did not receive a CDMS diagnosis ( p < 0.0001). Several studies have assessed the value of the CVS in MS patients and confirmed its ability to distinguish MS lesions from their mimics with good sensitivity and specificity; those studies used a range of scanners with various magnetic fields’ strengths: 1.5T scanners, 14 , 15 3 T scanners, 6 , 13 and 7T scanners. 8 , 11 For example, Tallantyre et al conducted a 7T MRI study to assess the CVS in 28 MS patients with a total of 901 lesions and 17 non-MS patients with a total of 428 lesions and determined a 40% cutoff for differentiating CDMS patients from non-MS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean percentage of CV-positive lesions was significantly higher in patients who received a CDMS diagnosis from the TC and ATC groups as compared to patients who did not receive a CDMS diagnosis ( p < 0.0001). Several studies have assessed the value of the CVS in MS patients and confirmed its ability to distinguish MS lesions from their mimics with good sensitivity and specificity; those studies used a range of scanners with various magnetic fields’ strengths: 1.5T scanners, 14 , 15 3 T scanners, 6 , 13 and 7T scanners. 8 , 11 For example, Tallantyre et al conducted a 7T MRI study to assess the CVS in 28 MS patients with a total of 901 lesions and 17 non-MS patients with a total of 428 lesions and determined a 40% cutoff for differentiating CDMS patients from non-MS patients.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Anan et al conducted a study in Egyptian patients using a 1.5T MRI scanner and found that the CVS had a specificity of 100% for detecting MS lesions when the load of CV-positive lesions was ≥ 44.24%. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CVS has been observing in all MS stages as a hypo-intense line or dot caused by paramagnetic substances and a contrast agent [13]. According to North American Imaging in Multiple Sclerosis guidelines that's recommends standardization to define the CVS, as the following [11,12]: a) Lesions appear as a centric hypo-intensity, as a central line or central dot according to the slice's position, either parallel or perpendicular to the vein. b) Vein must be crossing the lesion center.…”
Section: Definition Of Central Vein Signmentioning
confidence: 99%
“…These veins have been clearly observed at the center of WM lesions [9]. They can be detecting using various T2* weighted imaging sequences [6] such as 3D T2*-gradient echo [3], susceptibilityweighted image [12], and T2*-WI with EPI [11]. They are known as central vein signs and show up as a line having low signal intensity [6].…”
mentioning
confidence: 99%